A STUDY TO EVALUATE THE EFFECT OF ADDING CLONIDINE TO ROPIVACAINE FOR AXILLARY PLEXUS BLOCKADE - RAJMALA, JAISWAL; TEENA, BANSAL; SANDEEP, MEHTA; GEETA, AHLAWAT (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Aims and objectives- The present study was undertaken to evaluate the effect of adding Clonidine to Ropivacaine for axillary plexus blockade. Â Material and methods- A total of 60 adult patients having physical status grade I or II according to American Society of Anaesthesiologists ( ASA ) undergoing hand or forearm surgery under axillary plexus blockade using nerve stimulator were included in the study. Patients were randomly allocated to one of the two groups. Each group consisted of 30 patients. Â Group 1 patients received 35 ml of Ropivacaine 0.5 % + 1 ml of normal saline. Group 2 patients received 35 ml of Ropivacaine + 1 ml of clonidine ( 150 Âµg). Â Sensory block, motor block and sedation were assessed every 5 minutes for 30 minutes. Postoperatively assessment was done every 15 minutes till complete regression of sensory and motor block. Â Results- Mean sensory onset time in patients of group 1 was 26.48 Â± 7.88 min and in patients of group 2 was 26.55 Â± 8.06 min, which was insignificant statistically. Patients of group 1 had a mean motor onset time 35.51 Â± 10.4 min and patients of group 2 had a mean motor onset time 37.06 Â± 14.19min, the difference being statistically comparable. Mean duration of sensory block in patients of group 1 was 422 Â± 163.10 min and in patients of group 2 was 438 Â± 133.93 min, which was statistically comparable. Patients belonging to group 1 had a mean duration of motor block 404 Â± 160.60 min and patients belonging to group 2 had a mean duration of motor block 388 Â± 151.63 min, which was statistically comparable. Â Conclusion- Addition of Clonidine ( 150 Âµg) is of no benefit in the onset and duration of axillary plexus block.